The Audio-Visual Text: Subtitling and Dubbing Different Genres - Pettit, Zoë (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis article explores the complexity of the audio-visual text, comprised of both verbal and non-verbal components, and how this impacts upon foreign language subtitling and dubbing. Reference is made to a selection of audio-visual genres: the film, television series, news programme and documentary, in order to demonstrate the extent to which a particular genre influences translation. This article examines the interaction between language and image, between the verbal (concentrating on the spoken word) and the non-verbal (with specific reference to gesture and vocal intonation). The multi-semiotic nature of the audio-visual medium is stressed throughout.